Design, Analysis And Prototyping Of Endosurgical Trocar - Mohd Senusi, Shahrullizam (Universiti Sains Malaysia, 2004)
Nowadays, laparoscopy surgery has become the first option choose by the patient to do their treatment because of the advantages and efficiency of this surgery compare to the conventional open surgery. But, there are certain problem facing in the main instrument of this surgery which is trocar. The disadvantages and weaknesses of this equipment are the cost of this equipment are quite high because we have to import from the other countries (no company in Malaysia produced this product) and its not comfortable because we have to used 3 to 4 trocar in the surgery depend on the procedure. Beside that’s this trocar also have weaknesses in the geometry, reliability and others. So in this research and development project, we investigate the correlation theory and solve this problem facing and then come out with new generation design of the trocar with more efficiency and sophisticated. This design will be modelled by IDEAS (Integrated Design Engineering Analysis Software) software. Then, this design will be analysed using simulation application in this software to find out whether this design qualifies the requirement and specification needed. In this analysis, we will find out the maximum stress and displacement in the trocar when applied certain load and this stress test normally known as finite element analysis (FEA). The stress occurred depend on the types of the material used to make trocar such as polymers, elastomers and others and we will found out what is the best material to fabricate this trocar. After the analysis test, this model file will be transfered to the igl format for rapid prototyping machine. This machine will fabricate the prototype of this model.